Modern model of integral risk evaluation of diseases with temporary disability in the workers of modern mining and smelting industry of Ukraine (Environment & Health, 2019)
Objective: We harmonized the method for the analysis and evaluation of the morbidity associated with the conditions of work, with international standards.Materials and methods: We used hygienic, epidemiological, mathematical and statistical methods in the study.The main group was represented by 19 033 workers of 8 leading mining and smelting enterprises. Control group included 6270 persons who were not exposed to harmful production factors during the course of their work. The study of the incidence of temporary disability was conducted on the basis of the analytical treatment of the disability letters and the report on the causes of temporary disability (form TN-23) for 5 years (2010-2014).Results: We proposed an approach to the estimation of the risk of morbidity with a temporary disability, which, unlike the current one, allows not only to assess the level of the morbidity but also to identify the causes of its change and give a quantitative assessment of the factors affecting it: industrial harmful factors, medical care, quality of professional selection, etc. The quantitative correlation between these factors is a solid ground for the development of preventive measures which allow reducing the level of professional pathology by 7-15 % and preserve from 7 to 40 years of labour losses for the state and enterprises. According to the results of our research, the risk of the development of general diseases is higher in the main group in the workers of the underground mining of iron ore (RR=0.127), open mining of iron ore (RR=0.173), and metallurgical production (RR=0.161) than in the control group, and the ratio of the chances to have an occupational disease (OR) is 0.0516, 0.041, and 0.0061, respectively. The workers of main professions have a high relative risk (RR) of development the incidence of TBV which varies from 9.5 to 52.1.The etiological part of the professional factors in the development of diseases with TBP is 94.7-98.1 %, which indicates a high degree of connection of the morbidity with the conditions of work and a very high professional risk factor for the development of the risk of morbidity with a temporary disability at the workplace.Conclusions: Obtained parameters of morbidity, calculated on the basis of the analysis of the incidence of temporary disability, are necessary for the assessment of the risk of the development of professional and professionally determined pathology, while integral parameters, taking into account the incidence of diseases and the severity of the consequences, are crucial.
Keywords: occupational risk; incidence with temporary disability; integral assessment; mining and smelting industry